Contribuições especiais: perfil constitucional - Alcântara, Julianna Vasconcelos de (2007)
The present work has as objective of study, the special contributions, a special type of taxes. Such exaction is disciplined in art.149 of the Federal Constitution, which presents its main characteristics: the destination of the product of its collection to one determined mean and its non-restitution. From the analysis of some of the special contributions, such as of expenditure of the service of public illumination, of the FGTS, the ones instituted by the Complementary Law nº 110/2001, the confederative and the assistive, it was noticed that they did not have the previously cited characteristics. For this account, in order to facilitate the understanding of this work, I started to call these special contributions of pseudo-contributions, since they did not fit to the constitutional aspect. Those conclusions happened because of the study of the Federal Constitution, doctrine and jurisprudence referring to the subject in question.